Nonlinear analysis of RC structure with massive infill wall exposed to shake table - Onat, Onur (2016)
This study aims to present nonlinear time history analysis results of double leaf cavity wall (DLCW) reinforced concrete structure exposed to shake table tests. Simulation of the model was done by a Finite Element (FE) program. Shake table experiment was performed at the National Civil Engineering Laboratory in Lisbon, Portugal. The results of the experiment was compared with numeric DLCW model and numeric model of reinforced concrete structure with unreinforced masonry wall (URM). Both DLCW and URM models have two bays and two stories. Dimensions of the tested structure and finite element models are 1:1.5 scaled according to Cauchy Froude similitude law. The URM model has no experimental results but the purpose is to compare us performance level with the DLCW model. Results of the analysis were compared with experimental response and were evaluated according to ASCE/SEI 41-06 code.